Comparative Efficacy of Diclofenac Sodium and Gabapentin against Post-Operative Pain as Pre-Emptive Analgesia in Laparotomy - Saud Hussain, Ahmad Ali, Tauseef Jawaid, Atif Ahmed, Wajid Ali, Shaheer Azhar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To assess the relative effectiveness of diclofenac sodium and gabapentin as preventive analgesics for post-operative pain management in patients having laparotomy. Study Design: Present study was a comparative controlled trial conducted at random. Methodology: Current comparative controlled trial was conducted at random fashion in different surgical and pharmacology departments of Pakistan from December 2022 to June 2023. There were a total of 100 individuals having laparotomy therefore 600 mg capsule of Gabapentin and 100 mg sustain released combination therapy was given to the every patient one hour before to going into the procedure room under doctors direct supervision. All patients were put to sleep using the conventional general anesthetic approach. The patient was moved to the recovery area next to the operating theater once the procedure and extraction were finished and their pain was measured 1to 31 minutes. Finally, all patients were shifted to the ward where the intensity of their pain were measured 60, 121, 241 and 361 minutes respectively. The intermediate time of admission and operation were noted regularly. The bio-statistic version SPSS 2020 were applied for the description of raw data. Results: The mean standard deviation levels of age, gender, BMI, surgery duration and average anesthesia time in both Group-X and Group-Y individuals with gabapentin and diclofenac sodium were (57.18±18.04, 58.21±1.03), (67.11±01.02, 67.11±01.01), (33.10±01.04, 33.10±01.04), (28.10 ± 1.01), (27.11 ±1.01), (118.01±01.01), (128.01±02.02) showed a significant (P≤ 0.05) change. The pain ratings for gabapentin was (9.01±04.01) and diclofenac sodium was (15.25±02.03) for the 361-minute interval. 12-hour period or 721 minutes Compared to Diclofenac sodium, which exhibits a pain intensity of (14.61±04.05), gabapentin showed a considerable decline in pain. Conclusion: The study's findings showed that administering a single oral dosage of gabapentin as a preventive analgesic to patients having major abdominal operations is beneficial for managing post-operative pain since the medication's effects linger longer and decrease the need for rescue analgesics. Keywords: Gabapentin, Laparotomy, Anticonvulsants, glycopyrrolate, analgesics, surgery, abdominal, gynecological.